2016
DOI: 10.22267/rus.161802.36
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización del consumo de pescado y mariscos en población universitaria de la ciudad de Medellín - Colombia

Abstract: Restrepo-Betancurt LF, Rodríguez-Espinosa H, Valencia D. Caracterización del consumo de pescado y mariscos en población universitaria de la ciudad de Medellín -Colombia. Univ. Salud. 2016; 18(2):257-265. DOI: http://dx.doi.org/10.22267/rus.161802.36 Resumen Introducción: El conocimiento relacionado con el consumo de pescado es de vital importancia para establecer estrategias que permitan mejorar su consumo en esquemas de alimentación saludable. Objetivo: Identificar preferencias y frecuencia de consumo de p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
1
5
0
3
Order By: Relevance
“…Regarding shellfish, respondents preferred to consume shrimp and prawn. These results coincide with the research conducted in 2015 by Restrepo-Betancourt et al (36), who found that the preferred species of university students in the city of Medellín were tuna, tilapia, trout and shrimp; in turn, Gamboa-Delgado et al administered another survey to university students in Bucaramanga, and also found that they preferred trout, snapper and tuna (24). In 2005, Hererra-Arias et al (37) found a high prevalence of Salmonella spp.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding shellfish, respondents preferred to consume shrimp and prawn. These results coincide with the research conducted in 2015 by Restrepo-Betancourt et al (36), who found that the preferred species of university students in the city of Medellín were tuna, tilapia, trout and shrimp; in turn, Gamboa-Delgado et al administered another survey to university students in Bucaramanga, and also found that they preferred trout, snapper and tuna (24). In 2005, Hererra-Arias et al (37) found a high prevalence of Salmonella spp.…”
Section: Discussionsupporting
confidence: 89%
“…Además para Restrepo-Betancurt et al (2016) el sexo de termina el consumo de pescado de universitarios en Colombia, permitiéndose la promoción del consumo de pescado.…”
Section: Estos Resultados Concuerdan Con Los Planteados Porunclassified
“…Según Restrepo-Betancurt et al, (2016) en la ciudad de Medellín (Colombia), los factores que influye en las preferencias del consumo de pescado en los universitarios son el sexo, tipo de universidad y nivel socioeconómico.…”
Section: Factores Que Influyen El Consumo De Pescadounclassified
“…The presence of such parasites in armed snook fish is concerning because it is a species in great demand by commercial fisheries 15 and, on Colombia's Pacifiic coast, it is caught mainly This research has yielded important results that can be used to guide public policy in the fisheries, food quality and health sectors, with respect to a potential emerging disease in our country. Protection of human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The armed snook is a species of significant economic importance and is a preferred species for consumption by the local population 15 . It is distributed along the tropical and subtropical coasts of the Pacific and the American Atlantic.…”
Section: Introductionmentioning
confidence: 99%